Evaluation of European coeliac disease risk variants in a north Indian population - Senapati, Sabyasachi (Eur J Hum Genet, 2015)
Studies in European populations have contributed to a better understanding of the genetics of complex diseases, for example, in coeliac disease (CeD), studies of over 23 000 European samples have reported association to the HLA locus and another 39 loci. However, these associations have not been evaluated in detail in other ethnicities. We sought to better understand how disease-associated loci that have been mapped in Europeans translate to a disease risk for a population with a different ethnic background. We therefore performed a validation of European risk loci for CeD in 497 cases and 736 controls of north Indian origin. Using a dense-genotyping platform (Immunochip), we confirmed the strong association to the HLA region (rs2854275, P=8.2 × 10(−49)). Three loci showed suggestive association (rs4948256, P=9.3 × 10(−7), rs4758538, P=8.6 × 10(−5) and rs17080877, P=2.7 × 10(−5)). We directly replicated five previously reported European variants (P<0.05; mapping to loci harbouring FASLG/TNFSF18, SCHIP1/IL12A, PFKFB3/PRKCQ, ZMIZ1 and ICOSLG). Using a transferability test, we further confirmed association at PFKFB3/PRKCQ (rs2387397, P=2.8 × 10(−4)) and PTPRK/THEMIS (rs55743914, P=3.4 × 10(−4)). The north Indian population has a higher degree of consanguinity than Europeans and we therefore explored the role of recessively acting variants, which replicated the HLA locus (rs9271850, P=3.7 × 10(−23)) and suggested a role of additional four loci. To our knowledge, this is the first replication study of CeD variants in a non-European population.